2018
DOI: 10.2147/idr.s173468
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient ertapenem therapy in an ESBL-high-prevalence area: an efficacy, safety, and cost study

Abstract: IntroductionOutpatient parenteral antimicrobial therapy is a safe, effective, and convenient way of administering antimicrobials for a wide variety of infections. So far there are no reports on the efficacy of outpatient antimicrobial therapy in Mexico. Our objective was to determine the outcomes, safety, and cost of outpatient ertapenem therapy (OET) in our hospital.Patients and methodsA case series of 99 patients that received intravenous OET was conducted. The primary outcomes were clinical cure, relapse, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 21 publications
2
9
1
Order By: Relevance
“…In our study, OPAT was used most frequently for UTI, and E coli was found to be the most frequent causative agent. Similar to our study, the most common diagnosis was reported as UTI by Ortiz‐Alvarez et al 11 In many studies, the diagnoses of UTI and BJI were found to be the most frequent diagnoses of the patients who were treated in OPAT units 12 . Although UTI was the most prevalent diagnosis, the total number of saved BD was higher in patients with BJI.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, OPAT was used most frequently for UTI, and E coli was found to be the most frequent causative agent. Similar to our study, the most common diagnosis was reported as UTI by Ortiz‐Alvarez et al 11 In many studies, the diagnoses of UTI and BJI were found to be the most frequent diagnoses of the patients who were treated in OPAT units 12 . Although UTI was the most prevalent diagnosis, the total number of saved BD was higher in patients with BJI.…”
Section: Discussionsupporting
confidence: 88%
“…Our relapse and reinfection rates (32.6% and 17.9% respectively) were much higher than those in two other studies that reported relapse rates between 15% and 22% and reinfection rates 5.5% and 18% in different patients groups. [22][23][24]26 This Turkey. 15,16 Ertapenem resistance in urinary pathogens in Turkey is reported to range between 5.3% and 14.8%.…”
Section: Discussionmentioning
confidence: 99%
“…21 The use of ertapenem for OPAT was reported earlier in cUTIs with microbiologic eradication rates between 54.1% and 90% and with higher rates (92% and 96%) of clinical success. [22][23][24][25][26] OPAT for UTIs is a practical way of treating patients who do not need hospitalization but require IV antibiotic treatment. 22,27 OPAT was reported as safe and cost-effective 24,26 and more preferable for healthcare professionals and for patients than inpatient care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OPAT was equally effective, safer and significantly less expensive than inpatient care [13]. In Mexico, outpatient ertapenem therapy was studied in an ESBL-high-prevalence area and the treatment course was found to be effective, safe and cost-saving when compared to inpatient care [14].…”
Section: Discussionmentioning
confidence: 99%